Presentation - Hipólito, Rodrigo (Revista do Colóquio, 2025)
This edition of the Colóquio Journal is as extensive and varied as the previous one, which is related to the continuity of the publication and the opening of the doctorate in arts at PPGA-UFES. This second point, however, does not mean that the Colóquio will tend to close itself to receiving works only from postgraduate students, with no minimum limit on the number of titles for individual authors. We continue with our editorial policy focused on the breadth of voices and free research, both inside and outside the university. As can be seen in our previous editions, we prioritize the publication of a variety of works that explore the relationship between art, society and contemporary thought, in organizations that reveal an interdisciplinary dialogue between research. In this sense, our editorial process prioritizes the complexity of current cultural phenomena.
Keywords: presentation; journal; contemporary art